2006
DOI: 10.1038/sj.sc.3102000
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of neuropathic pain after non-traumatic spinal cord lesion

Abstract: Study design: Retrospective register study. Objective: To investigate the predictive value of the following parameters for the development of neuropathic pain after non-traumatic spinal cord lesion: that is age at onset of spinal cord disease, gender, completeness of lesion, level of lesion, and aetiology. Setting: A unit for patients with post-acute traumatic and non-traumatic spinal cord lesions in the greater area of Stockholm, Sweden. Method: All patients with non-traumatic spinal cord lesions visiting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 22 publications
2
42
0
Order By: Relevance
“…Siddall and Loeser found a prevalence of 65% 6 . However, in a study specifically on neuropathic pain, Werhagen et al 18 found a prevalence of 26% in a group of 402 patients with traumatic lesion in Switzerland, which corroborates our study 17 . They also did not find any correlation between occurrences of pain and patients' ages and level and type of lesion (complete or incomplete).…”
Section: Discussionsupporting
confidence: 82%
“…Siddall and Loeser found a prevalence of 65% 6 . However, in a study specifically on neuropathic pain, Werhagen et al 18 found a prevalence of 26% in a group of 402 patients with traumatic lesion in Switzerland, which corroborates our study 17 . They also did not find any correlation between occurrences of pain and patients' ages and level and type of lesion (complete or incomplete).…”
Section: Discussionsupporting
confidence: 82%
“…One of the most important secondary complications of SCI that negatively affects patient quality of life is neuropathic pain. 9 Werhagen et al 14 reported that SCI patients aged 450 years had the highest prevalence of neuropathic pain (58%). In the present study, 50.7% of the older patients and 34.7% of the younger patients reported neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Logistic regression analysis in the present study showed that age X60 years was a significant risk factor for neuropathic pain, but that the level of injury, completeness of injury, gender and diabetes were not, as previously reported. 9,14 We think additional research on the factors that predispose older SCI patients to neuropathic pain is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Our prevalence of 52% is lower when compared with other reports in the SCI literature. 22,25 Prospective information to characterise the study population further, such as with the use of formal psychological and pain assessments, would add weight to our findings. Future prospective studies may examine this.…”
Section: Discussionmentioning
confidence: 99%